To Carnival! : a celebration in Saint Lucia - Paul, Baptiste (Barefoot Books, 2021)
When Melba oversleeps and misses her ride to town, she is worried she will miss Carnival, but when she finds a new way to the festivities, she collects her own parade of friends and discovers that the real celebration is the love that surrounds her.